A sol–gel route to synthesize SiO2/TiO2 well-ordered nanocrystalline mesoporous photocatalysts through ionic liquid control. (19th February 2015) - Zhang, Fengfeng; Sun, Dayin; Yu, Chunling; Yin, Yuxin; Dai, Hongyi; Shao, Guolin
Abstract : SiO2 /TiO2 composite photocatalysts were prepared through a sol–gel method, using an ionic liquid (IL), 1-butyl-3-methylimidazole bromide ([Bmim]Br), as a structure controlling agent. Abstract : SiO2 /TiO2 composite photocatalysts were prepared through a sol–gel method, using an ionic liquid (IL), 1-butyl-3-methylimidazole bromide ([Bmim]Br), as a structure controlling agent. The obtained materials were characterized by Fourier transform (FT-IR) spectroscopy, powder X-ray diffraction (XRD), N2 adsorption–desorption isotherm measurements, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The as-prepared TiO2 nanoparticles present an anatase crystal phase even without being calcined, and show better photocatalytic performance in the degradation of reactive brilliant blue. The results showed that a suitable aging concentration of IL was beneficial to the growth of crystalline particles, but harmful if more than the limit. Micelle State Charge Field (MSCF) leading to lyotropic liquid crystalline mesophases was first presented to describe the role of IL in the formation of crystals and porosities.